Pengaruh PAD, DAK Dan DBH Terhadap Pertumbuhan Ekonomi Melalui Belanja Langsung Di Kabupaten Merangin - Selamet Edi Sucipto (ILTIZAM Journal of Shariah Economics Research, 2022)
The purpose of this research is 1) To analyze the effect of PAD, DAK and DBH on Direct Expenditure in Merangin District during 2001-2015. 2) To analyze the effect of PAD, DAK, and DBH on Economic Growth through Direct Spending in Merangin District during 2001-2015. Based on result of research by using path analysis and using multiple linier regression analysis, using 2 (two) equation that is 1) Influence of PAD, DAK and DBH to Direct Shopping. 2) Effect of PAD, DAK, DBH and Direct Spending on Economic Growth. From the result of path analysis for the first equation that has been done, it can be concluded that able to influence direct expenditure is DAK variable, while PAD and DBH have no effect to direct expenditure. DAK has a positive influence on direct expenditure. Direct DAK can have a big and positive impact on direct expenditure, whereas if the indirect effect of DAK on direct expenditure through PAD and DBH can have a positive effect but the effect is more keil compared to the direct influence of DAK on direct expenditure in Merangin District. From result of path analysis for second equation which have been done hence can be drawn conclusion able to influence economic growth through direct expenditure is variable of DAK and DBH, while PAD has no effect to economic growth. DAK, DBH and direct expenditure have a positive influence on economic growth. Direct DAK, DBH and direct expenditures have a big and positive impact on economic growth, while the indirect effect of DAK and DBH on economic growth through direct expenditure is less than direct influence of DAK and DBH on economic growth.